2023
DOI: 10.37575/h/edu/230027
|View full text |Cite
|
Sign up to set email alerts
|

Journalists' Objectivity via Social Media: Jordan

Omar Al-Zoubi,
Normahfuzah Ahmad,
Khalaf Tahat

Abstract: Journalists play an essential role in society through their daily news practice. The news produced must be correct. Fair and balanced reporting makes an informed public. These elements are part of objectivity in the news. However, social media have challenged many aspects of journalism. With the emergence of social media platforms, journalists have become more prone to deviating from journalistic objectivity. Instantaneity has challenged many journalists to practice their journalistic work objectively via soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…This emphasizes the commitment of journalists participating in the study to be responsible toward society and condemn news that does not adhere to neutrality (Nwanne, 2014). This is in line with the study by Al-Zoubi et al (2024) which confirmed that Jordanian journalists are committed to social responsibility in their social media pages, despite the challenges they face. Albeit neutrality itself remains a contestable journalistic issue.…”
Section: Discussionsupporting
confidence: 80%
“…This emphasizes the commitment of journalists participating in the study to be responsible toward society and condemn news that does not adhere to neutrality (Nwanne, 2014). This is in line with the study by Al-Zoubi et al (2024) which confirmed that Jordanian journalists are committed to social responsibility in their social media pages, despite the challenges they face. Albeit neutrality itself remains a contestable journalistic issue.…”
Section: Discussionsupporting
confidence: 80%